Factors influencing adherence to tuberculosis treatment in Asmara, Eritrea: a qualitative study - Frezghi Hidray Gebreweld; Meron Mehari Kifle; Fitusm Eyob Gebremicheal; Leban Lebahati Simel; Meron Mebrahtu Gezae; Shewit Sibhatu Ghebreyesus; Yordanos Tesfamariam Mengsteab; Nebiat Ghirmay Wahd (BMC, 2018)
Abstract Background Non-adherence to tuberculosis (TB) treatment is an important barrier for TB prevention and control. Poor adherence may result in prolonged disease infectiousness, drug resistance, relapse and death. The aim of this study was to assess factors influencing adherence to tuberculosis treatment in selected health facilities in Asmara, Eritrea. Methods A qualitative study which included in-depth interviews with 12 TB patients, three focus group discussions in selected health facilities in which one group comprised eight patients and key informant interviews with three health workers. Data analysis was done by translating and transcribing the verbatim of the interviews and focus group discussions. Transcribed data was then analysed using thematic framework procedure. Results This study found that patients lacked knowledge about the cause, transmission and duration of treatment of TB. The most common reason mentioned for discontinuing treatment was the patient "felt cured". Almost half of the respondents did not know the standard treatment duration and the consequences they face if they halt treatment. Patients reported losing their job when their diagnosis was known, were too ill to continue working or unable to find daily work due to time-consuming treatment arrangements. With few exceptions, the majority of patients reported that the short distance to the clinic encouraged them to attend regular treatment follow-up. Most of the respondents were unable to get enough food, leading to stress and feelings of hopelessness. Lack of social support for most of the patients was a critical factor for adherence as were stigma, medication side effects and long treatment duration. Recognized as an enabler to treatment adherence, health workers had good communication and positive attitude towards their patients. Conclusion Lack of knowledge, loss of income, stigma and lack of social support, drug side effects and long treatment duration emerged as important barriers for treatment adherence. Short distances to health facilities, good communication and accepting attitude of health care providers emerged as enablers for treatment adherence. For better treatment adherence, comprehensive health education at treatment sites, patient's family members and the community at large and strengthening of social support structures need to be addressed.